The Principle of Irony in Kierkegaard’s Philosophy - Šliogeris, Arvydas (Problemos, 1978)
The article analyses the social roots of the origin of ironic attitude towards reality and the “ontological” meaning of the principle of irony in S. Kierkegaard’s philosophy. Kierkegaard distinguished two types of irony – banal, i.e., the irony of German romanticists, and existentialist, i.e., the irony of Socrates. The author of the article interprets irony as the individual-psychological reflection of alienation processes, conditioned by socio-economic factors.